Effect of temperature and diet on wound healing in Atlantic salmon (Salmo salar L.) - Jensen, L. B.; Wahli, T.; McGurk, C.; Eriksen, T. B.; Obach, A.; Waagbø, R.; Handler, A.; Tafalla Piñeiro, Carolina (Fish Physiology and Biochemistry, 2015)
Compromised skin integrity of farmed Atlantic salmon, commonly occurring under low temperature and stressful conditions, has major impacts on animal welfare and economic productivity. Even fish with minimal scale loss and minor wounds can suffer from secondary infections, causing downgrading and mortalities. Wound healing is a complex process, where water temperature and nutrition play key roles. In this study, Atlantic salmon (260 g) were held at different water temperatures (4 or 12 °C) and fed three different diets for 10 weeks, before artificial wounds were inflicted and the wound healing process monitored for 2 weeks. The fish were fed either a control diet, a diet supplemented with zinc (Zn) or a diet containing a combination of functional ingredients in addition to Zn. The effect of diet was assessed through subjective and quantitative skin histology and the transcription of skin-associated chemokines. Histology confirmed that wound healing was faster at 12 °C. The epidermis was more organised, and image analyses of digitised skin slides showed that fish fed diets with added Zn had a significantly larger area of the epidermis covered by mucous cells in the deeper layers after 2 weeks, representing more advanced healing progression. Constitutive levels of the newly described chemokines, herein named CK 11A, B and C, confirmed their preferential expression in skin compared to other tissues. Contrasting modulation profiles at 4 and 12 °C were seen for all three chemokines during the wound healing time course, while the Zn-supplemented diets significantly increased the expression of CK 11A and B during the first 24 h of the healing phase. © 2015, Springer Science+Business Media Dordrecht.